2017
DOI: 10.1016/j.ehj.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure, the forgotten enemy: Toward implementation of national safety program

Abstract: Radiation safety is an important counterpart in all facilities utilizing ionizing radiations. The concept of radiation safety has always been a hot topic, especially with the late reports pointing to increased hazards with chronic radiation exposure. Adopting a nationwide radiation safety program is considered one of the most urging topics, and is a conjoint responsibility of multiple disciplines within the health facility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Here, the average value on the 10-point Likert scale is 6.03. The fact that nurses have such a relatively clear knowledge of radiation safety policies is encouraging, given the importance of radiation protection to those exposed to it [ 25 ]. They indicated that staff safety is crucial when operating in a regulated area involving exposure to radiation but lack of understanding of the concept of the inverse square law of radiation protection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the average value on the 10-point Likert scale is 6.03. The fact that nurses have such a relatively clear knowledge of radiation safety policies is encouraging, given the importance of radiation protection to those exposed to it [ 25 ]. They indicated that staff safety is crucial when operating in a regulated area involving exposure to radiation but lack of understanding of the concept of the inverse square law of radiation protection.…”
Section: Discussionmentioning
confidence: 99%
“…e study found that participating nurses scored higher in their radiation safety expertise than their knowledge of the other two aspects of radiation knowledge (guidelines of radiation use and radiation physics). Here, the average value on the 10-point Likert scale is 6.03. e fact that nurses have such a relatively clear knowledge of radiation safety policies is encouraging, given the importance of radiation protection to those exposed to it [25]. ey indicated that staff safety is crucial when operating in a regulated area involving exposure to radiation but lack of understanding of the concept of the inverse square law of radiation protection.…”
Section: Discussionmentioning
confidence: 99%
“…According to the principle of As Low As Reasonably Achievable (ALARA), radiation exposure during medical procedures should be limited as there is no known safe procedural dose of radiation for medical procedures 15 . Electrophysiology laboratory staff and operators, in comparison to the general population, are exposed to 2x risk of skin lesions, 3x risk of cancer, 6.3x risk of cataracts, and 7.1x risk of orthopedic injuries 16–19 . In addition, electrophysiology patients are exposed to an average of approximately 15 mSv during an average atrial fibrillation ablation 12 .…”
Section: Why Reduce Fluoroscopy?mentioning
confidence: 99%
“…15 Electrophysiology laboratory staff and operators, in comparison to the general population, are exposed to 2x risk of skin lesions, 3x risk of cancer, 6.3x risk of cataracts, and 7.1x risk of orthopedic injuries. [16][17][18][19] In addition, electrophysiology patients are exposed to an average of approximately 15 mSv during an average atrial fibrillation ablation. 12 This is an equivalent radiation exposure of 750 chest X-rays.…”
Section: Why Reduce Fluoroscopy?mentioning
confidence: 99%
“…With the improvement of health services and an aging population, the use of radioisotopes and ionizing radiation in diagnosis and treatment have steadily increased [ 13 ]. Global estimates show that approximately 3.6 billion radiation examinations on average were conducted annually from 2000 to 2007, and the use of diagnostic procedures involving radiation has more than doubled during the past 25 years in many countries [ 14 16 ]. Thus, medical radiation workers have gradually become the largest occupational group exposed to artificial radiation sources [ 17 ].…”
Section: Introductionmentioning
confidence: 99%